2022
DOI: 10.1186/s12862-022-01966-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of hatching enzymes and their paralogous genes in vertebrates

Abstract: Background Hatching is identified as one of the most important events in the reproduction of oviparous vertebrates. The genes for hatching enzymes, which are vital in the hatching process, are conserved among vertebrates. However, especially in teleost, it is difficult to trace their molecular evolution in detail due to the presence of other C6astacins, which are the subfamily to which the genes for hatching enzymes belong and are highly diverged. In particular, the hatching enzyme genes are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In egg-laying vertebrates like fishes, amphibians, reptiles and birds, a specialized group of astacin MPs termed hatching enzymes has evolved ( Nagasawa et al, 2022 ). They are absent from mammals and involved in the cleavage of the eggshell.…”
Section: Resultsmentioning
confidence: 99%
“…In egg-laying vertebrates like fishes, amphibians, reptiles and birds, a specialized group of astacin MPs termed hatching enzymes has evolved ( Nagasawa et al, 2022 ). They are absent from mammals and involved in the cleavage of the eggshell.…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous study, patristacin genes can be found between the c1qtnf4 and atp6v0d1 genes, in a region that received the name Pastn‐synteny‐set (Nagasawa et al, 2022). On the same chromosome, but far from the Pastn‐synteny‐set region, other c6ast genes (nephrosin and pactacin) can be found in a region located between the fadd and mtch2 genes, termed Npsn&Pac‐synteny‐set (Nagasawa et al, 2022). In this study, we first searched c6ast genes of 33 species in 18 different orders among Euteleostei using both syntenic regions as an index (Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…The assembled whole-genome sequence data were obtained from NCBI (all species and accession numbers used in this study are listed in Table S1). To find the coding region of the c6ast gene, we performed TBLASTN search using the amino acid sequences of the c6ast genes, identified in our previous study (Nagasawa et al, 2022), as a query, and selected the genes showing more than 65% similarity. To exclude intronic sequences of c6ast genes, we performed the genewise2 using the c6ast sequences of closely related species as references.…”
Section: Homology-based Prediction Of Coding Sequences and Genomic Sy...mentioning
confidence: 99%
See 2 more Smart Citations